Effect of moisture conservation and integrated nutrient management on summer maize (Zea mays) in Kandahar, Afghanistan - MOZAFARI, S HAMIDULLAH; DASS, ANCHAL; CHOUDHARY, ANIL K; RAIHAN, O; RAJANNA, G A (The Indian Journal of Agricultural Sciences, 2020)
Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar, Afghanistan during summer season of 2017 to determine the effect of moisture conservation practices and INM on maize growth, productivity, profitability and resource-use efficiency. Planting maize on raised-beds along with wheat crop residues-mulch (3 t/ha) significantly improved the growth, yield attributes, yield, net returns, monetary-efficiency, production-efficiency and water-productivity over flat-bed planting. Applying 50% RDF + FYM (10 t/ha) and 2-foliar sprays of urea (2%) first at knee-high stage and second at tasseling stage, resulted in the highest growth, yield, production efficiency and water productivity, which was in general at par with 100% RDF. These results suggest that summer maize crop in Kandahar and other similar regions may be planted on raised beds mulched with crop residue (3 t/ha) and fertilized using INM approach to enhance productivity, profitability and resource-use efficiency.